Dynamic Chromatin Modification Sustains Epithelial-Mesenchymal Transition following Inducible Expression of Snail-1 - Sarah Javaid; Jianmin Zhang; Endre Anderssen; Josh C. Black; Ben S. Wittner; Ken Tajima; David T. Ting; Gromoslaw A. Smolen; Matthew Zubrowski; Rushil Desai; Shyamala Maheswaran; Sridhar Ramaswamy; et al. (Cell Reports, 2013)
Epithelial-mesenchymal transition (EMT) is thought to contribute to cancer metastasis, but its underlying mechanisms are not well understood. To define early steps in this cellular transformation, we analyzed human mammary epithelial cells with tightly regulated expression of Snail-1, a master regulator of EMT. After Snail-1 induction, epithelial markers were repressed within 6 hr, and mesenchymal genes were induced at 24 hr. Snail-1 binding to its target promoters was transient (6–48 hr) despite continued protein expression, and it was followed by both transient and long-lasting chromatin changes. Pharmacological inhibition of selected histone acetylation and demethylation pathways suppressed the induction as well as the maintenance of Snail-1-mediated EMT. Thus, EMT involves an epigenetic switch that may be prevented or reversed with the use of small-molecule inhibitors of chromatin modifiers.